The Role of Teachers in Implementing STEAM Learning in Early Childhood Education: A Systematic Literature Review - Annisa Aulia Dewi; Hibana Yusuf; Lailatu Rohmah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to examine the role of teachers in the implementation of STEAM learning (Science, Technology, Engineering, Arts, and Mathematics). The method employed was a Systematic Literature Review (SLR) of 15 national journal articles published between 2021 and 2025, obtained through Google Scholar and selected based on inclusion criteria and research objectives. The results of the analysis indicate that teachers play a central role as facilitators, mediators, and designers of STEAM learning, which is capable of enhancing 21st-century skills such as critical thinking, creativity, communication, and collaboration in children. However, several challenges remain, including an incomplete understanding of the STEAM concept, limited facilities and infrastructure, and minimal integration of Islamic values in learning practices. This study emphasizes the importance of strengthening teacher capacity through training, innovative learning strategies, and policy support to optimize value-based STEAM implementation in order to shape children’s character from an early age.